Inundações urbanas no semiarido nordestino: o caso da cidade de Pau dos Ferros - RN - Costa, Franklin Roberto da (2010)
The Apodi river basin, particularly within the snippet that crosses Pau dos Ferros - RN city, place anthropogenic actions that interfere in the dynamic environment by modifying the local landscape. The reflection of these actions can be seen in the floods that occur in rainy periods (February to may) virtually every year in the city. It is important to stress that the project of integration of the waters of the San Francisco basin with the northern basin of Northeastern will perennial the main channel of the river basin, and generate greater impacts in the region. This work sought to define a methodology able to delimit areas susceptible to flooding in cities of semiarid Northeast based on the Pau dos Ferros RN city. The dissertation is divided into two chapters and introduction. The introduction presents a theoretical frame based on discussion of the concept of risk, their main characteristics and subdivisions; floods; geotecnologies; Apodi River basin; municipal data Pau dos Ferros RN and design integration of Francisco basin with the northern basins Northeast. The first chapter evaluates the urban expansion process between 1987 and 2008, delimiting the flood areas and analyzes the relationship between urban growth and retention areas. The second chapter identifies the flood risk areas in the Pau dos Ferros city. The methodology used was based on tools of geographic information system GIS from software SPRING/INPE 5.1, as well as bibliographical, satellite images, aerial photographs and field activities. The results obtained enabled view the rapid expansion of the urban area of Pau dos Ferros, which has doubled in a period of 22 years. The population density checks with greater intensity in South-central portion of the city, in flood areas and not flood (Cap. 01). It was noted also that some neighborhoods along the River Apodi are susceptible to more instances of flooding ranging from minimum to maximum, while in neighborhoods near the Riacho Cajazeiras floods occur to a lesser extent because of altimetry higher and lower water volume. (Cap. 02). It is expected that this work will help in the preparation of flood risk municipal map subsidising managers in implementing public policies targeted to the softening of urban flood-related issues in Pau dos Ferros RN and serve as a model for mapping of other cities with similar characteristics analyzed in this work